Influence of saddle setback on knee joint forces in cycling - Menard, M.; Domalain, M.; Decatoire, A.; Lacouture, P. (Sports Biomechanics, 2020)
Knee functional disorders are one of the most common lower extremity non-traumatic injuries reported by cyclists. Incorrect bicycle configuration may predispose cyclist to injury but the evidence of an effect of saddle setback on knee pain remains inconclusive. The aim of this study was to determine the effect of saddle setback on knee joint forces during pedalling using a musculoskeletal modelling approach. Ten cyclists were assessed under three saddle setback conditions (range of changes in saddle position ~6 cm) while pedalling at a steady power output of 200 W and cadence of 90 rpm. A cycling musculoskeletal model was developed and knee joint forces were estimated using an inverse dynamics method associated with a static optimisation procedure. Our results indicate that moving the saddle forwards was not associated with an increase of patellofemoral joint forces. On the contrary, the tibiofemoral mean and peak compression force were 14 and 15% higher in the Backward than in the Forward condition, respectively. The peak compression force was related to neither pedal force nor quadriceps muscle force but coincided with the eccentric contraction of knee flexor muscles. These findings should benefit bike fitting practitioners and coaches in the design of specific training/rehabilitation protocols